2011
DOI: 10.1177/0748233711399308
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and ACE enhancing potential of Pankajakasthuri in fluoride toxicity: Anin vitrostudy on mammalian lungs

Abstract: Fluoride toxicity occurs due to high concentrations of fluoride in water sources or anthropogenic causes. The aim of the present study was to investigate the effects of an Ayurvedic drug--Pankajakasthuri (PK)--in relation to fluoride-induced toxicity in mammalian lungs. The results indicated that sodium fluoride increased lipid peroxidation and decreased enzymatic and non-enzymatic antioxidants in a concentration-dependent manner in lungs. The antioxidant potential of the lungs was suppressed maximally at 10 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The results also showed changes in biomarkers of oxidative stress as evidenced by a decrease of reduced glutathione and an increase in peroxynitrite concentrations. Fluoride is known to reduce intracellular GSH levels and inhibit various enzymes that require GSH as a cofactor (66). Besides, (14) reported that, a reduction in GSH content and in the activity of antioxidant enzymes in the liver of rats exposed to SF indicating an impaired function of the hepatic antioxidant defense system (67) associated to an increase of LPO (56).…”
Section: Resultsmentioning
confidence: 99%
“…The results also showed changes in biomarkers of oxidative stress as evidenced by a decrease of reduced glutathione and an increase in peroxynitrite concentrations. Fluoride is known to reduce intracellular GSH levels and inhibit various enzymes that require GSH as a cofactor (66). Besides, (14) reported that, a reduction in GSH content and in the activity of antioxidant enzymes in the liver of rats exposed to SF indicating an impaired function of the hepatic antioxidant defense system (67) associated to an increase of LPO (56).…”
Section: Resultsmentioning
confidence: 99%
“…The activity of ACE localized in erythrocyte membranes is a significant indicator of OP poisoning severity (13). In previous studies (chronic and subchronic exposure) in rats and humans, acute OP poisoning erythrocyte ACE activity was not significantly different than levels in healthy controls (Tinoco & Halperine, 1998;Öğüt et al, 2011). On the contrary, in a rat study of subchronic OP exposure, erythrocyte ACE activity and TBARS levels were found to be significantly lower in the toxicity group compared to healthy controls (Lukaszewicz-Hussain & Moniuszko-Jakoniuk, 2005).…”
Section: Discussionmentioning
confidence: 97%
“…The results also showed changes in biomarkers of oxidative stress as evidenced by a decrease of reduced glutathione and an increase in peroxynitrite concentrations. Fluoride is known to reduce intracellular GSH levels and inhibit various enzymes that require GSH as a cofactor (67).Besides, (1) reported that, a reduction in GSH content and in the activity of antioxidant enzymes in the liver of rats exposed to SF indicating an impaired function of the hepatic antioxidant defense system (27) associated to an increase of LPO (72). This deterioration overlaps with the elimination of H 2 O 2 and LPO products and causes their accumulation in the cells leading to the damage of cell membranes and may affect the activity of these enzymes which constituting the cell anti-oxidative system (37).…”
Section: Discussionmentioning
confidence: 99%